A complex fracture of the hyoid bone and the larynx after a bicycle accident – Case report and review of literature - Sievert, Matti; Eisenhut, Felix; Iro, Heinrich; Traxdorf, Maximilian; Müller, Susanna; Taha, Lava (International Journal of Surgery Case Reports, 2021)
Introduction and importance: Reports about laryngeal trauma and fractures of the hyoid bone are rare in the literature. Most cases are forensic cases and the results of postmortem analysis. Traumatic larynx and hyoid bone fractures represent a rare but important differential diagnosis of the common symptom hoarseness. Case presentation: A 60-year-old female patient presented with unclear dysphonia and globus sensation following intubation for a surgical treatment for a lower leg fracture after a bicycle accident two months ago. Endoscopy and the computed tomography (CT) of the neck revealed a fixed and immobile fractured piece of the larynx, a hyoid bone fracture and a pseudarthrosis between the greater horn of the hyoid bone and the upper edge of the thyroid cartilage. The hyoid bone fracture led to a distortion of the supraglottis. After surgical removal of the fractured part of the hyoid bone and the pseudarthrosis separation, the supraglottis appeared symmetrical again. Four weeks after surgery the patient was symptom-free. Clinical discussion: Though combined hyoid bone and larynx fractures after traumatic injuries are rare, they represent an important differential diagnosis in trauma patients with dysphagia or dysphonia. The clinical symptoms can vary and occur immediately or within a latent period taking weeks or months until the proper diagnosis. Depending on the symptoms, surgical management can be effective. Conclusion: An isolated partial resection of the hyoid bone with separation of the pseudarthrosis is a reasonable therapeutic option and can lead to completely resolving symptom. Preoperatively, a CT provides further valuable information.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Case report; Computed tomography; Dysphagia; Dysphonia; Hyoid bone fracture; Laryngeal trauma